Breast Reconstruction in a Coronavirus Disease 2019 Hub - Andrea Lisa, MD; Andrea Battistini, MD; Silvia Giannasi, MD; Alessandra Veronesi, MD; Valeria Bandi, MD; Luca Maione, MD; Valeriano Vinci, MD; Corrado Tinterri, MD; Marco Babbini, MD; Marco Klinger, MD (Plastic and Reconstructive Surgery, Global Open, 2020)
Background:. The coronavirus disease 2019 (COVID-19) pandemic presented a dramatic challenge to healthcare systems. Humanitas Clinical and Research Hospital (Rozzano, MI, Italy) was declared a regional hub for the treatment of COVID-19 patients. Our plastic surgery team, in consultation with our breast surgery colleagues, decided to perform immediate implant-based breast reconstruction for patients undergoing mastectomy for cancer. In this report, we present our experience performing breast reconstruction with a new protocol in the first month following the COVID-19 pandemic in the most affected region in Italy. Methods:. We adopted a new protocol to treat patients with breast cancer during the COVID-19 pandemic. The main goals of our protocol were to reduce the risk of COVID-19 spread for both patients and clinicians, postpone nononcologic and more advanced surgery, develop rapid recovery for early patient discharge (within 24 hours from surgery) through pain management, and finally reduce postoperative consultations. Results:. The protocol was applied to 51 patients between early March and early April 2020. After 1 month, we decided to retrospectively review our experience. We found no significant differences in terms of postoperative pain and complication rate compared with our data in the pre-COVID period. Conclusion:. Our new protocol is safe and effective, enabling tumor resection and immediate implant-based breast reconstruction, without increasing risks to the patient or staff.